Voting over Taxes: The Case of Tax Evasion - Christian Traxler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper studies majority voting on taxes when tax evasion is possible. We characterize the voting equilibrium where the agent with median taxed income is pivotal. Since the ranking of true incomes does not necessarily correspond to the ranking of taxed incomes, the decisive voter can differ from the median income receiver. In this case, we find unconventional patterns of redistribution, e.g. from the middle class to the poor and the rich. Furthermore, we show that majority voting can lead to an inefficiently low level of taxation – despite a right-skewed income distribution. Hence, the classical over-provision result might turn around, once tax evasion is taken into account.
urn:nbn:de:bvb:19-epub-1188-9
Keywords: H26; H72; D6; 330; Majority Voting; Tax Evasion; Welfare Analysis; Redistribution; Steuerflucht; Wohlfahrtsanalyse; Theorie